2020
DOI: 10.3390/insects11120876
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Enzymatic Hydrolysis on the Functional Properties, Antioxidant Activity and Protein Structure of Black Soldier Fly (Hermetia illucens) Protein

Abstract: The effects of chemical protein extraction, and enzymatic hydrolysis with Alcalase, papain and pepsin, on the functional properties, antioxidant activity, amino acid composition and protein structure of black soldier fly (H. illucens) larval protein were examined. Alcalase hydrolysates had the highest degree of hydrolysis (p < 0.05), with the highest hydrolysate and oil fraction yield (p < 0.05). Pepsin hydrolysates showed the lowest oil holding capacity (p < 0.05), whereas no significant differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…A drastic reduction in ES of AF Et (60.93 ± 3.84%) was noticed, which is a typical characteristic exhibited by extensively enzymatically hydrolysed proteins due to excessive protein degradation negatively affecting the interfacial absorptivity and molecular rearrangement at the surface [37,39]. The results were analogous to the data reported by Batish et al [18]. Perhaps a stringent method of ES determination proposed for edible insects could be adapted for future functionality investigation to obtain comparable results [38].…”
Section: Protein Functional Properties and Quality Parameterssupporting
confidence: 82%
See 2 more Smart Citations
“…A drastic reduction in ES of AF Et (60.93 ± 3.84%) was noticed, which is a typical characteristic exhibited by extensively enzymatically hydrolysed proteins due to excessive protein degradation negatively affecting the interfacial absorptivity and molecular rearrangement at the surface [37,39]. The results were analogous to the data reported by Batish et al [18]. Perhaps a stringent method of ES determination proposed for edible insects could be adapted for future functionality investigation to obtain comparable results [38].…”
Section: Protein Functional Properties and Quality Parameterssupporting
confidence: 82%
“…Processes 2021, 9, x FOR PEER REVIEW 4 of 2 solid fraction proteins (Table 3), as the aqueous fraction constitutes only hydrophilic pro tein hydrolysates. The OBC for BSFL protein concentrate, when compared to protein hy drolysates, did not vary significantly, but the values reported were almost two time higher (4 g oil/g DM) in a recent study [18]. The OBC of protein concentrates and flour prepared from other insect species such as Tenebrio molitor, Gryllodes sigillatus and Sch socerca gregaria were within the range of 1.7 to 3.3 g oil/g DM [38].…”
Section: Protein Functional Properties and Quality Parametersmentioning
confidence: 74%
See 1 more Smart Citation
“…The hydrolysis condition of ep-JPH for 6, 12, 18, and 24 h showed the DH values of 52.20%, 54.01%, 54.50%, and 55.41% (Table 1). During the pepsin hydrolysis, the peptide bonds of a jellyfish protein were hydrolysed and provided a short-chain peptide and free amino acid [38], depending on hydrolysis factors, including pepsin concentration, hydrolysis time, and temperature. In this study, the pepsin hydrolysed jellyfish sample at the hydrolysis time of 12, 18, 24 h showed similar DH values, and these values were not significantly different.…”
Section: Effect Of Hydrolysis Time Of Pepsin On Soluble Protein Content Degree Of Hydrolysis Antioxidant Activity (Dpph) and Salt Contentmentioning
confidence: 99%
“…A study reported on the emulsifying properties of BSFL protein sample and its hydrolyzed products by different enzymes. The study revealed that the non-hydrolyzed sample showed improved emulsifying stability compared to the sample hydrolyzed by alcalase, (DH = 18.4%), papain (DH = 15.34%) and pepsin (DH = 9.8) [ 43 ].…”
Section: Resultsmentioning
confidence: 99%